A Comparative Evaluation of Wide-Bandgap Semiconductors for High-Performance Domestic Induction Heating - Sezer Aslan; Metin Ozturk; Nihan Altintas (Energies, 2023)
This paper presents a comparative evaluation of wide-bandgap power semiconductor devices for domestic induction heating application, which is currently a serious alternative to traditional heating techniques. In the induction heating system, the power transferred to the output depends on the equivalent resistance of the load, and the resistance depends on the operating frequency. Due to the switching characteristics of wide-bandgap power semiconductor devices, an induction heating system can be operated at higher operating frequencies. In this study, SiC and Si semiconductor devices are used in the comparison. These devices are compared according to different evaluation issues such as the turn-off energy losses, turn-off times, current fall time, the power losses of the internal diodes, and the conduction voltage drops issues. To perform the proposed evaluation, the series-resonant half-bridge inverter, which is frequently used in state-of-the-art induction heating systems, has been selected. The device suitability in an induction heating system is analyzed with the help of a test circuit. A comparison is made in terms of criteria determined by using the selected switches in the experimental circuit, which is operated in the 200 W to 1800 W power range and 45 kHz to 125 kHz switching frequency range. System efficiency is measured as 97.3% when Si IGBT is used. In the case of using SiC cascode JFET, the efficiency of the system is increased up to 99%.